3 - Globalisation and Migration in Africa - John K. Akokpari, (African Sociological Review, 2000)
The paper argues that there is a growing interconnection between globalisation on the one hand, and migration (both intra- and interstate) on the other. In general migration in Africa is largely informal and undocumented, making accurate data on the phenomenon extremely scant. This notwithstanding, there is evidence of the phenomenal increase in the wave of migration on the continent. The conventional causes of migration, including conflicts, political oppression, economic crisis and environmental factors, have in recent years been reinforced by globalisation which unleashes fresh pressures that either facilitate or compound the already huge and seemingly unmanageable migration problematique on the continent. The paper demonstrates the various ways by which globalisation impacts on migration. Among other things, it notes the unencumbered movement of capital accompanied by capitalists across state borders, the formation of regional trading blocs as a logical response to the imperatives of globalisation, which promote the free movement of people within regions, and the deepening of disparities between countries, which spawns the movement of people from the poor to the more affluent countries. Further, the paper analyses the impact of globalisation on Africa's already fragile environment and argues that there is a growing tendency for diminishing environmental resources to generate conflicts between user constituencies. Such conflicts displace people and exert migratory pressures. It is argued further that, while globalisation promotes greater migration, most African states, especially the relatively affluent, are increasingly closing their borders to immi grants because of a variety of reasons, including the fear of emigrants engaging in criminal activities. The paper concludes that the imbalance between increased migration and shrinking immigration opportunities leads to the adoption of informal alternatives by emigrants to get to their destinations.